IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN KUALITAS PENDIDIKAN ISLAM DI MIN KOTA BUKITTINGGI - Febriani, Susanda; M, Iswantir; Sari, Fatma (Jurnal Al-Fatih, 2023)
Education is a process carried out by teachers and students when learning is carried out in the classroom. At this time the school began implementing an independent curriculum. The implementation of independent curriculum management in improving the quality of education at the Bukittinggi City MIN involves the education unit committee and various stakeholders including parents, organizations, various centers, under the coordination and supervision of the Bukittinggi City Education Office. The purpose of the study was to analyze the management of: (1) learning organization; (2) learning planning; (3) evaluation, mentoring and professional development. The research used a qualitative approach with descriptive methods. The research location is MIN Bukittinggi City. The research subjects are the implementers of the independent curriculum management, namely the principal, vice principal, teachers and learning committee. The results showed that the management of the implementation of the independent curriculum was effective and meaningful so as to improve the quality of education at MIN Kota Bukittinggi.